2022
DOI: 10.1002/arch.21888
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of RNA interference using nanocarrier‐based transdermal dsRNA delivery system in the woolly apple aphid, Eriosoma lanigerum

Abstract: RNA interference (RNAi) is an essential approach for studying gene function and has been considered as a promising strategy for pest control. However, RNAi method has not been conducted in Woolly apple aphid (Eriosoma lanigerum Hausmann), one of the most damaging apple pests in the world. In the study, we investigated the efficacy of RNAi of V-ATPase subunit D (ATPD), an efficacious target for RNAi in other insects, in E. lanigerum by a transdermal double-stranded RNA (dsRNA) delivery system with nanocarriers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
3
0
4
Order By: Relevance
“…The RNAi efficiency of acetylcholinesterase ( AChE ) gene silencing in P. xylostella can be improved by concatemerised dsRNAs (C‐dsRNA) (Sharath et al., 2019). Nanocarriers can increase the RNAi efficiency of the V‐ATPase subunit D ( ATPD ) gene of Woolly apple aphid from 40.5% to 98.5% (Guo et al., 2022). Since the genes with lower transcript abundance required less dsRNA for silencing (Zhu & Palli, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The RNAi efficiency of acetylcholinesterase ( AChE ) gene silencing in P. xylostella can be improved by concatemerised dsRNAs (C‐dsRNA) (Sharath et al., 2019). Nanocarriers can increase the RNAi efficiency of the V‐ATPase subunit D ( ATPD ) gene of Woolly apple aphid from 40.5% to 98.5% (Guo et al., 2022). Since the genes with lower transcript abundance required less dsRNA for silencing (Zhu & Palli, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have evaluated the insecticidal potential of targeting H + V-ATPase subunits in several insect species, including a variety of insect pests, showing strong negative impacts on growth and survival ( Ahmed, 2016 ; Sato et al, 2019 ; Rahmani and Bandani, 2021 ; Guo et al, 2022 ; Liu et al, 2022 ; Shi et al, 2022 ; Zeng et al, 2022 ). So far, the majority of these studies focused on targeting the different subunits of the V 1 domain of these proton pumps.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also investigated the RNAi efficacy of the ATPD gene in woolly apple aphids (Eriosoma lanigerum) via a nanocarrier-mediated transdermal dsRNA delivery system. Their results suggested that the interference efficiency was greatly increased using nanocarriers and induced high aphid mortality [86]. The nanocarrier-delivered RNAi method was also used to silence the flightin, vestigial (vg), and Ultrabithorax (Ubx) genes, which suppressed the wing development in M. persicae [85,91].…”
Section: Other Delivery-method-mediated Gene Silencing For Aphid Controlmentioning
confidence: 99%